Content of conventional therapy for the severely affected arm during subacute rehabilitation after stroke: An analysis of physiotherapy and occupational therapy practice. (16th January 2017) - de Jong, Lex D.; van Wijck, Frederike; Stewart, Roy E.; Geurts, Alexander C.H.; Dijkstra, Pieter U.
Abstract: Background and Purpose: Physiotherapy (PT) and occupational therapy (OT) are key professions providing treatment for the arm after stroke; however, knowledge about the content of these treatments is scant. Detailed data are needed to replicate interventions, evaluate their effective components, and evaluate PT and OT practice. This paper describes PT and OT treatment for the severely affected arm in terms of duration, content according to components and categories of the International Classification of Human Functioning, Disability and Health, and to analyze differences between professions. Methods: Design: This is a retrospective analysis of randomized trial data. Participants: 46 patients after stroke with poor arm motor control recruited from inpatient neurological units from three rehabilitation centers in the Netherlands. Procedure: PTs and OTs recorded duration and content of arm treatment interventions for 8 weeks using a bespoke treatment schedule with 15 International Classification of Human Functioning, Disability and Health categories. Results: PTs and OTs spent on average 4–7 min per treatment session (30 min) on arm treatment. OTs spent significantly more time providing arm treatment and treatment at the activities level than PTs. PTs spent 79% of their arm treatment time on body functions, OTs 41%. OTs spent significantly more time on "moving around using transportation, " "self care, " and "household tasks" categories. Conclusions: Patients after stroke with a severely affected arm and an unfavorable prognosis for arm motor recovery receive little arm‐oriented PT and OT. Therapists spent most arm treatment time on body functions. There was a considerable overlap in the content of PT and OT in 12 of the 15 categories. Results can be generalized only to patients with poor arm motor control and may not represent practice in other countries.